2001
DOI: 10.1016/s0378-1097(01)00198-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the genus Bartonella: what is the current knowledge?

Abstract: Species of the genus Bartonella are involved in an increasing variety of human diseases. In addition to the 14 currently recognized species, several Bartonella strains have been recovered from a wide range of wild and domestic mammals in Europe and America. Such a high diversity of geographic distributions, animal reservoirs, arthropod vectors and pathogenic properties makes clarification of our knowledge about the phylogeny of Bartonella species necessary. Phylogenetic data have been inferred mainly from 16S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
(96 reference statements)
2
22
0
Order By: Relevance
“…In the past decade, a number of new Bartonella species have been described (6,15,27) and comparisons of 16S rDNA sequences have led to many taxonomic changes in the genus Bartonella (7,11). Although comparison of 16S rDNA gene sequences has been useful in phylogenetic studies at the genus level (41), its use has been questioned in studies at the species level (21; M. Hasegawa and T. Hashimoto, Letter, Nature 361:23, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, a number of new Bartonella species have been described (6,15,27) and comparisons of 16S rDNA sequences have led to many taxonomic changes in the genus Bartonella (7,11). Although comparison of 16S rDNA gene sequences has been useful in phylogenetic studies at the genus level (41), its use has been questioned in studies at the species level (21; M. Hasegawa and T. Hashimoto, Letter, Nature 361:23, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Recently the number of Bartonella species isolated has increased markedly (5,6,15,27), and the bacteria are considered emerging pathogens involved in an increasing number of recognized diseases (1,28,38). Currently, 19 Bartonella species are recognized, and all are associated with mammalian hosts.…”
mentioning
confidence: 99%
“…Species of the genus Bartonella are associated with an increasing array of human diseases, among which bacillary angiomatosis and peliosis hepatitis in immunocompromised patients. 13 Mammalian reservoirs of Bartonella include small carnivores and rodents, 14 their transmission rate depends on the Bartonella strain, host, and specific vector. Historical data on rickettsiosis and bartonellosis in the Democratic Republic of the Congo (DRC) (former Zaire) are fragmentary, but serological tests have reported Rickettsia conorii, Rickettsia prowazekii, and R. typhi as early as the 1950s.…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of comparative analysis of DNA sequence data to delineate Bartonella species has already been demonstrated (Lawson & Collins, 1996), and the application of this approach as the primary criterion for species definition has recently been proposed (La Scola et al, 2003). Several genetic loci have been used for the characterization of Bartonella isolates (Houpikian & Raoult, 2001), but comparative analysis of citrate synthase gene (gltA) fragments remains the most commonly used approach for identifying bartonellae and inferring evolutionary relationships within the genus (Birtles & Raoult, 1996). Studies of inferred evolutionary relationships among Bartonella species have revealed that species parasitizing the same or similar host species are not necessarily closely related.…”
Section: Introductionmentioning
confidence: 99%